A critical examination of the influence of material characteristics and extruder geometry on 3D printing of cementitious binders. (September 2020) - Nair, Sooraj A.O.; Panda, Subhashree; Santhanam, Manu; Sant, Gaurav; Neithalath, Narayanan
Abstract: Extrusion pressure-displacement tests on cementitious pastes with multiple starting materials and differing particle packing, subjected to different extrusion geometries are reported. The steady state extrusion pressure (equivalent to extrusion yield stress) and the deadzone length (static zone of material buildup at die entry) are determined from the pressure-displacement response to characterize the extrudability and/or printability. A unique "geometric ratio" is used to account for the effects of barrel-die geometry on paste extrusion. The ratio of extrusion yield stress (25–75 kPa) to the measured shear yield stress (50–300 Pa), the deadzone length, and the measured-to-designed filament volume at a given flow rate (print speed) are found to remain relatively invariant with geometric ratio for mixtures with high degree of microstructural packing, and thus better extrudability and shape stability. This paper marries materials- and process-related issues and, could pave the way for test methods for 3D printable mixture qualification.